Mild cognitive impairment and transitions in cognitive status in the Systolic Blood Pressure Intervention Trial (SPRINT). (31st December 2021) - Gaussoin, Sarah A; Pajewski, Nicholas M; Chelune, Gordon; Cleveland, Maryjo; Crowe, Michael G; Launer, Lenore J; Lerner, Alan J; Martindale‐Adams, Jennifer; Nichols, Linda O; Ogrocki, Paula K; Sachs, Bonnie C; Sink, Kaycee M; et al.
Abstract: Background: The Systolic Blood Pressure Intervention Trial (SPRINT) demonstrated a significant reduction in the occurrence of mild cognitive impairment (MCI) for adults with hypertension randomly assigned to intensive systolic blood pressure (SBP) lowering and a similar but non‐significant effect on incidence of dementia.. Given that individuals with MCI are at greater risk of progressing to dementia, an open question from the trial is the frequency of progression in cognitive status subsequent to an adjudication of MCI, and whether this associates with intensive SBP lowering. Method: Randomized trial of community‐dwelling adults (≥50 years) with hypertension. Participants were randomized to a SBP goal of <120 mm Hg (intensive treatment; n=4678) or <140 mm Hg (standard treatment; n=4683). Adjudication of MCI or dementia followed standardized procedures by a panel of expert clinicians. Multistate survival models were used to examine transitions in cognitive status between normal cognitive function, MCI, and dementia, accounting for the competing risk of death. Result: Among 9361 randomized participants (mean age, 67.9 years; 3332 women [35.6%]), 91.5% completed at least 1 follow‐up cognitive assessment over a median follow‐up of 5.1 years. Based on multistate modeling, from a state of normal cognitive function, the risk of transitioning to dementia in the next 2 years was 1.1% [95% Confidence Interval (CI): 1.0% to 1.3%]), with 2.3% [95% CI: 2.1% to 2.5%] of participants dying over that same interval. Subsequent to an adjudication of MCI, the probability of progressing to dementia in the next 2 years increased to 6.4% [95% CI: 5.3% to 7.8%], with the risk of death increasing to 8.2% [95% CI: 6.9% to 9.7%]. We did not observe any significant associations between treatment groups and transition risk within the multistate model, though power for these analyses was likely limited given the focus on complex transitions between multiple outcomes. Conclusion: An adjudication of MCI in SPRINT was associated with an increased risk of progression to dementia and death in the following 2 years, highlighting the relevance of MCI as an outcome both within SPRINT and for future prevention trials of cognitive impairment.